MCM10 compensates for Myc‐induced DNA replication stress in breast cancer stem‐like cells. Issue 3 (22nd January 2021) - Murayama, Takahiko; Takeuchi, Yasuto; Yamawaki, Kaoru; Natsume, Toyoaki; Li, Mengjiao; Marcela, Rojas‐Chaverra N.; Nishimura, Tatsunori; Kogure, Yuta; Nakata, Asuka; Tominaga, Kana; Sasahara, Asako; Yano, Masao; et al.
Abstract: Cancer stem‐like cells (CSCs) induce drug resistance and recurrence of tumors when they experience DNA replication stress. However, the mechanisms underlying DNA replication stress in CSCs and its compensation remain unclear. Here, we demonstrate that upregulated c‐Myc expression induces stronger DNA replication stress in patient‐derived breast CSCs than in differentiated cancer cells. Our results suggest critical roles for mini‐chromosome maintenance protein 10 (MCM10), a firing (activating) factor of DNA replication origins, to compensate for DNA replication stress in CSCs. MCM10 expression is upregulated in CSCs and is maintained by c‐Myc. c‐Myc‐dependent collisions between RNA transcription and DNA replication machinery may occur in nuclei, thereby causing DNA replication stress. MCM10 may activate dormant replication origins close to these collisions to ensure the progression of replication. Moreover, patient‐derived breast CSCs were found to be dependent on MCM10 for their maintenance, even after enrichment for CSCs that were resistant to paclitaxel, the standard chemotherapeutic agent. Further, MCM10 depletion decreased the growth of cancer cells, but not of normal cells. Therefore, MCM10 may robustly compensate for DNA replication stress and facilitate genome duplication in cancer cells in the S‐phase, which is more pronounced in CSCs. Overall, we provide a preclinical rationale to target the c‐Myc‐MCM10 axis for preventing drug resistance and recurrence of tumors. Abstract : We provide evidence that upregulated c‐Myc expression induces stronger DNA replication stress in patient‐derived breast cancer stem‐like cells than in differentiated cancer cells. Our results suggest critical roles for mini‐chromosome maintenance protein 10 (MCM10), which is a firing (activating) factor of the DNA replication origins, to compensate for the DNA replication stress.